2021
DOI: 10.3389/fmolb.2021.641734
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-6 in Vascular Health and Disease

Abstract: IL-6 is usually described as a pleiotropic cytokine produced in response to tissue injury or infection. As a pro-inflammatory cytokine, IL-6 activates innate and adaptative immune responses. IL-6 is released in the innate immune response by leukocytes as well as stromal cells upon pattern recognition receptor activation. IL-6 then recruits immune cells and triggers B and T cell response. Dysregulated IL-6 activity is associated with pathologies involving chronic inflammation and autoimmunity, including atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 147 publications
(80 reference statements)
1
51
0
Order By: Relevance
“…A large number of studies have shown that IL-6 plays a key role in the progression of coronary atherosclerosis ( 20 , 21 ). IL-6 promotes the proliferation of neutrophils and monocytes as well as expression of adhesion molecules by vascular endothelial cells to enhance the local inflammatory response ( 22 ). In addition, IL-6 induces liver cells to synthesize fibrinogen and CRP ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that IL-6 plays a key role in the progression of coronary atherosclerosis ( 20 , 21 ). IL-6 promotes the proliferation of neutrophils and monocytes as well as expression of adhesion molecules by vascular endothelial cells to enhance the local inflammatory response ( 22 ). In addition, IL-6 induces liver cells to synthesize fibrinogen and CRP ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another exercise-induced cytokine (and classical myokine [ 187 ]) with prominent effects on the brain, and brain mitochondria, is interleukin-6 (IL-6) [ 188 ]. While IL-6 has been shown to regulate mitochondrial biogenesis in astrocytes [ 189 ], its mode of action is complex and can result in both pro- and anti-inflammatory outcomes [ 183 , 190 ].…”
Section: How Do Muscles Communicate With the Brain?mentioning
confidence: 99%
“…These facts indicate that exercise has some effects on the secretion of sIL-6R, and that the effects are different depending on the type of exercise. It was shown that cycling is a strenuous exercise that results in increased sIL-6R secretion [ 83 ]. Generally, mild exercise is better for health than strenuous exercise is, which may be due to the effects of sIL-6R secretion into plasma.…”
Section: Classical Signaling and Trans -Signaling Of Il-6mentioning
confidence: 99%